Dural Plasmacytoma with Meningeal Myelomatosis in a Patient with Multiple Myeloma - Nieves Gascón; Héctor Pérez-Montero; Sandra Guardado; Rafael D’Ambrosi; María Ángeles Cabeza; José Fermín Pérez-Regadera (Case Reports in Hematology)
Here, we describe the case of a 66-year-old male diagnosed with multiple myeloma who presented with generalized tonic-clonic seizures. Magnetic resonance imaging demonstrated a right solid extra-axial parieto-occipital lesion with typical characteristics of meningeal myelomatosis. Biopsy was performed, which diagnosed a dural plasmacytoma. Because of this, we started concomitant therapy with radiotherapy and lenalidomide, but the patient has a poor response to treatment and died few weeks after its initiation. Myelomatous involvement of the dura mater is a rare occurrence, given that only few cases were reported in the English literature. This presentation confers an ominous prognosis and must be a suspect diagnosis in patients diagnosed with multiple myeloma presenting neurological symptoms.